2021
DOI: 10.1038/s41598-021-91087-5
|View full text |Cite|
|
Sign up to set email alerts
|

Derangement of cell cycle markers in peripheral blood mononuclear cells of asthmatic patients as a reliable biomarker for asthma control

Abstract: In asthma, most of the identified biomarkers pertain to the Th2 phenotype and no known biomarkers have been verified for severe asthmatics. Therefore, identifying biomarkers using the integrative phenotype-genotype approach in severe asthma is needed. The study aims to identify novel biomarkers as genes or pathways representing the core drivers in asthma development, progression to the severe form, resistance to therapy, and tissue remodeling regardless of the sample cells or tissues examined. Comprehensive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 129 publications
0
9
0
Order By: Relevance
“…Identification of novel biomarkers can contribute to the patient classification, therapy response, and clinical outcome prediction 21 . In asthma, most identified biomarkers are limited to the Th2 phenotype, and no effective biomarkers have been verified for severe asthma 22 . Blood samples serve as an alternative to the challenging and costly approach of obtaining airways samples in severe asthma 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Identification of novel biomarkers can contribute to the patient classification, therapy response, and clinical outcome prediction 21 . In asthma, most identified biomarkers are limited to the Th2 phenotype, and no effective biomarkers have been verified for severe asthma 22 . Blood samples serve as an alternative to the challenging and costly approach of obtaining airways samples in severe asthma 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of new biomarkers aid in the categorization of patients, therapeutic response, and clinical outcome prediction [ 36 ]. Most biomarkers for asthma are confined to the Th2 phenotype, and no useful biomarkers for severe asthma have been confirmed in both children and adults [ 37 ]. Our work identified ten potential biomarkers in childhood asthma, including IL6 , IL4 , IL2 , IL13 , PTPRC , IL5 , IL33 , TBX21 , IL2RA , and STAT6 .…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of chemotaxis, migration, and myeloid cell trafficking and downregulation of B-lymphocyte development, hematopoietic progenitor cells, and lymphoid organ hypoplasia were observed in patients with severe asthma [63]. Hachin et al studied the blood transcriptome and found that genes GPRC5A, SFN, and ABCA1 were upregulated while genes SERPINE1, GPRC5A, SFN, ABCA1, MKI67, and RRM2 were downregulated in PBMCs from patients with severe uncontrolled asthma [64].…”
Section: Blood Cell Transcriptomics Of Asthmamentioning
confidence: 99%
“…Hachim et al identified total of 10 genes (GPRC5A, SFN, ABCA1, KRT8, TOP2A, SER-PINE1, ANLN, MKI67, NEK2, and RRM2) related to cell cycle and proliferation to be disturbed in the severe asthmatic bronchial epithelium and fibroblasts [64]. However, their study revealed that gene regulation varied across different tissues and asthma subtypes.…”
Section: Airway Epithelial Cell Transcriptomics Of Asthmamentioning
confidence: 99%